Globalization and bank efficiency nexus: empirical evidence from the Malaysian banking sector - Sufian, Fadzlan; Kamarudin, Fakarudin; Md Nassir, Annuar (Emerald Group Publishing, 2017)
Purpose: The purpose of this paper is to provide a new empirical evidence on the impact of economic globalization on the efficiency of the banking sector. The paper also investigates to what extent the internal (i.e. bank specific characteristics) and external (i.e. macroeconomic conditions) factors influence the efficiency of banks while controlling for the impact of the different dimensions of globalization. Design/methodology/approach: The analysis is confined into two stages. In the first stage, the authors employ the bias-corrected data envelopment analysis method to compute the efficiency of individual banks during the period 1999-2012. The authors then use bootstrap regressions to examine the impact of economic globalization on bank efficiency, while controlling for the potential impacts of contextual variables. Findings: The empirical findings indicate that the impacts of personal contacts, information flows, and cultural proximity seem to work in favor of Malaysian banks’ efficiency. A plausible reason could be due to the fact that capital account liberalization is usually accompanied by liberalization of the financial services sector, resulting in a greater competition and subsequently eroding monopolistic profits. The empirical findings also bring forth the importance of and political globalization in determining the efficiency of banks operating in the Malaysian banking sector. Originality/value: The present study aims to provide for the first time empirical evidence on the performance of the banking sector and to establish new empirical evidence on the impact of globalization. The empirical evidence on the impact of globalization on the banking sector is completely missing from the literature.